Analysing the Role of Religious Education in Improving the Work Ethic of MSME Owners - Muhammad Ade Kurnia Harahap; Abu Muna Almaududi Ausat; Suherlan Suherlan (Journal on Education, 2023)
MSMEs are an important sector in a country's economy. However, MSMEs in Indonesia still experience various problems. One of the factors that can affect the quality of human resources in MSMEs is work ethic. So, the role of religious education in improving the work ethic of MSME owners needs to be studied further. This study aims to explain the role of religious education in improving the work ethic of MSME owners and provide a deeper understanding of the factors that influence work ethic in MSMEs and how religious education can help improve the work ethic. This research is qualitative in nature. Data collection techniques include listening and recording important information to conduct data analysis through data reduction, data display, and conclusion drawing. The results of this study conclude that religious education can play an important role in improving the work ethic of MSME owners. The moral values and business ethics taught in religious education can help MSME owners to develop a good work ethic and build a sustainable successful business.